Work-Related Disease (WRD) - Umayyah, Siti Aisyah (Oshada, 2024)
Occupational Safety and Health (OSH) is a joint effort between employers and employees to increase productivity by creating a safe and healthy work environment. The importance of OSH as part of decent work is also understood through the concept of epidemiology, which considers the interaction between host, agent, and environment in the workplace. In this context, this paper formulates several questions related to occupational diseases (OD), their causes, the spectrum of OD, and methods for early detection of OD. This paper aims to understand the concept of OD, examine the causes and risks of OD, understand the spectrum of diseases related to OD, and identify methods for early detection of OD. The benefits include a source of information and insight for readers about the concept of OWD, reading material and references for students and the community, and a source of knowledge in the field of OSH in the workplace. Thus, this paper is expected to contribute to increasing understanding and awareness of the importance of OSH in creating a safe and healthy work environment.